2019
DOI: 10.1039/c9gc02598g
|View full text |Cite
|
Sign up to set email alerts
|

Grafting strategies for hydroxy groups of lignin for producing materials

Abstract: Lignin is one of the most abundant biopolymers on Earth and is considered as the primary resource of aromatic compounds. Recently, lignin has attracted attention from scientists and industrialists due to its inherent potential arising from its unique structure, which leads to its possible use in many applications.Many efforts have been made to ameliorate the reactivity and compatibility of lignin in different areas. Although methods have been proposed for endowing lignin with different properties, there contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(88 citation statements)
references
References 241 publications
0
69
0
3
Order By: Relevance
“…In past decades, billions of tons of non-biodegradable plastics have been produced, which is a significant source of pollution. As an abundant natural polymer, lignin could be integrated into plastics to fabricate high-value biodegradable materials with economic competitiveness (Sen et al, 2015;Kazzaz et al, 2019). Therefore, the preparation of composite materials by mixing lignin with various plastics had attracted attention.…”
Section: Lignin-plastic Compositesmentioning
confidence: 99%
“…In past decades, billions of tons of non-biodegradable plastics have been produced, which is a significant source of pollution. As an abundant natural polymer, lignin could be integrated into plastics to fabricate high-value biodegradable materials with economic competitiveness (Sen et al, 2015;Kazzaz et al, 2019). Therefore, the preparation of composite materials by mixing lignin with various plastics had attracted attention.…”
Section: Lignin-plastic Compositesmentioning
confidence: 99%
“…For methylolation, the reaction conditions are comparable (alkaline medium and temperature range of 25−90°C) to glyoxalation; however, shorter reaction times are typically applied due to the higher reactivity of formaldehyde compared to glyoxal. 110 From Table 1, it can be concluded that most of the studies applied a glyoxal solution to lignin (G/L), mass ratio between 0.1 and 1 (glyoxal is typically supplied as a 40 wt % solution). However, it is difficult to compare all glyoxal:lignin ratios applied in the different studies.…”
Section: ■ Glyoxalation Of Ligninmentioning
confidence: 99%
“…Signals at δ 3.9 to 3.6 are assigned to -OCH3 hydrogens and ~ δ 3.3 to -CH2 hydrogens from hydroxymethyl groups (Jiao et al 2018). During sulfomethylation, formaldehyde introduces a hydroxymethyl group into the lignin at the C5 position of the aromatic ring, which is the main reaction location in the sulfonation reaction with sodium sulfite (Yu et al 2013;Kazzaz et al 2019). Thus, the increase in the signal intensity in this region is due to the introduction of hydroxymethyl groups in the OSKL.…”
Section: H Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…The sulfomethylation reaction of lignin involves the addition of a methylene sulfonate group (-CH2SO3) into the aromatic ring, i.e., the C5 position of G-type lignin. Briefly, the precursors formaldehyde (CH2O) and sodium sulfite (Na2SO3) under determined reaction parameters combine to form sodium hydroxymethyl sulfonate, the reactive species responsible for introducing the sulfonic group into lignin (Meister 2002;Konduri and Fatehi 2015;Huang et al 2018;Kazzaz et al 2019). However, due to the complex and highly branched polyphenolic structure of lignin along with the sulfomethylation reaction conditions, different degrees of sulfonation and structural changes of lignin can be promoted, which could affect the depression performance of the lignin-derived product.…”
Section: Introductionmentioning
confidence: 99%